Monstruosité de l'héroïne: réécriture de Médée dans Chanson douce de Leïla Slimani. Issue 4 (19th July 2022) - Franco, David
Abstract: Leïla Slimani's Chanson douce draws an explicit parallel between its protagonist, Louise, a nanny who eventually kills the children she looks after, and the mythological figure of Medea, specifically Pierre Corneille's version of the Princess of Colchis. This article argues that the analogy between Louise and Medea, rather than restricting Louise to being exclusively monstrous because of the infanticide, highlights the paradoxical dimension of her character. Her monstrosity, in fact, is inseparable from her heroism. We will call upon Aristotle's principles of tragedy as well as Corneille's own theoretical writings — in which the playwright himself explains that his Médée, while a criminal, remains admirable — to show how Louise is able to portray herself as a simultaneously laudable and blameable character by affirming her allegiance to a classical ideal of dignity. The dramaturgical approach of the article shines a new light on the protagonist of this controversial novel, winner of the 2016 Prix Goncourt.